Perlindungan Dasar Laut Warisan Bersama Umat Manusia Rekonsiliasi Hukum Lingkungan dan Hukum Perang - Rivaldy, Aditya (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
The deep seabed beyond national jurisdiction, known as “the Area,” is governed by the principle of the Common Heritage of Mankind (CHM), designed to ensure its peaceful use and equitable benefit for all humanity. However, in the context of contemporary armed conflicts, the Area faces increasing vulnerability due to the legal inadequacies of International Humanitarian Law (IHL), which largely fails to account for complex environmental threats posed by modern warfare. This research critically examines the insufficiency of existing IHL principles—such as distinction, proportionality, and military necessity—to safeguard the Area’s ecological and legal integrity during hostilities. It further explores how the integration of peacetime International Environmental Law (IEL) and relevant customary norms may serve as a legal bridge to enhance environmental protection during armed conflict. Drawing on doctrinal legal analysis, authoritative case law, treaty interpretation, and recent policy developments, this study advocates for the continued application of environmental treaties and principles, such as UNCLOS and Principle 21 of the Stockholm Declaration, even amidst warfare. The findings suggest that IEL and customary norms offer a more robust framework to preserve the Area's protected status than IHL alone, provided their applicability is clearly affirmed through treaty interpretation, military doctrine, or international soft law. This legal reinforcement is essential to prevent the Area from becoming an ecological casualty of war and to uphold its status as a global commons